A latent profile analysis of doctors’ joy in work at public hospitals - Zhu, Weilin; Li, Jiayi; Wu, Liqun; Du, Fang; Zhou, Yi; Diao, Kaichuan; Zeng, Huatang (Frontiers in Psychology, 2024)
Introduction When doctors’ work stress increases, their joy in work decreases, severely affecting the quality of care and threatening patient safety. Analysis of the latent categories of joy in work of doctors in public hospitals and the differences in the characteristics of each category can help uncover hidden messages that enhance doctors’ joy in work. Methods Questionnaires were administered to 426 doctors working in public hospitals using the general information questionnaire and the public hospital doctor’s joy in work evaluation scale. Upon identifying their potential categories using latent profile analysis, chi-square test, and multinomial logistic regression were performed to analyze the differences in the characteristics of each category. Results The 426 public hospital doctors could be divided into three potential categories: “low joy in work” (11.27%), “medium joy in work” (59.86%), and “high joy in work” (28.87%). Most of the doctors did not have much joy in work, with 71.13% of them having “low to medium joy in work.” Doctors who work in secondary or tertiary hospitals, have a personnel agency or contract, and are older than 45 years are more likely to belong to the “low joy in work” category. Some of the protective factors are having an average monthly income (RMB) of 10,001–15,000 yuan and having a fair or good self-rated health status. Conclusion There are obvious classification characteristics of doctors’ level of joy in work. Hospital managers can take commensurate actions to improve their joy in work, thereby improving patient safety and the quality of medical services.